The impact of iatrogenic complications in oral surgery for the brain diseases’ diagnosis – a case report - Jolanta Białkowska-Głowacka; Kamila Rychlewska; Karol Więcek; Anna Janas-Naze (Journal of Education, Health and Sport, 2017)
The article presents a case of a patient, who underwent a lower third molar surgery, resulting a retained metal foreign body in mandible, which in turn caused numerous artifacts in the MRI of the brain and resulted in its false interpretation.